Design of a plastic injection mold (8 cavities) / Muhammad Fadzli Abdul Rahman and Md Zulkhairi Ismail - Abdul Rahman, Muhammad Fadzli; Ismail, Md Zulkhairi (Faculty of Mechanical Engineering, 2001)
This project work reports the design work on up-grading a mold die. A 2 cavities mold was up-graded to 8 cavities. This up-grading will increase the efficiency, time for one cycle, production rate and life time of mold. When the mold is up-graded to 8 cavities it becomes more economical and also will increase the life of the mold die. It is important for production of plastic parts like connector. This mold die has been designed according to standard design practice. The material for this mold must be considered carefully. From the assembly of the die detailed part drawings were made. Machining steps in processes such as E. D. M, WIRE CUT, MILLING, GRINDING are given. To ensure the quality of the mold after up-grading all relevant tests to be carried out are explained. Tests for the mold flow process to check the pressure drop, and the material flow balance inside the mold are suggested.